Creative accounting practices and measurement methods: Evidence from Turkey - Ata Ozkaya (Kiel Institute for the World Economy (IfW), 2014)
A fiscal rule imposed when the budget is not transparent yields more creative accounting to circumvent it and less fiscal adjustment, generating hidden deficits/debts in public sector. This study focuses on creative accounting practices of governments and adds to the literature by measuring hidden debts of the Turkish public sector ranging from the period 1989 to 2010. Accordingly, the author shows that the IMF has been misinformed, indeed has been misled by the Turkish authorities regarding the magnitude of public debt stock at the late 90'. The lacking information deteriorated the IMF' forecasts, which might be one of the main reasons for the failure of the IMF' planned fiscal consolidation at the outset of 2000-2001 crisis. The author' methodology can easily be adapted to any other country in order to identify the different margins on which governments can cheat and manipulate the Government Finance Statistics.
Keywords: E62; H61; H63; H83; 330; fiscal rules; creative accounting; contingent liabilities; hidden public debt; IMF policies